A simplistic unit cell model for sound absorption of cellular foams with fully/semi-open cells. (30th October 2015) - Yang, X.H.; Ren, S.W.; Wang, W.B.; Liu, X.; Xin, F.X.; Lu, T.J.
Abstract: We present a simplistic yet accurate unit cell model of sound absorption for highly porous foams having either fully-open or semi-open cells. Employing an idealized periodic cubic unit cell to mimic the foam topology, we establish an analytical model for predicting the sound absorption coefficient of the foam. Analytical links between key non-acoustic parameters (viscous permeability and flow tortuosity) and cellular topological characteristics are also established. For fully-open foams, the model requires only two morphological parameters, porosity and pore window size, significantly reducing the complexity of sound transport modeling. For semi-open foams, an additional parameter, open-pore rate representing the influence of thin membrane covering on pore window, is introduced. The analytical model predictions are compared with existing experimental data and numerical simulation results for polyurethane foams, with good agreement achieved.